Research on dynamic characteristics of reinforced concrete supported girder bridges strengthened by plate–truss combination - Pang, Mulin; Gou, Wenxin; Xie, Xiaoli; Meng, Donglin; Cao, Feng (Sound & Vibration, 2026)
Existing strengthening methods for reinforced concrete simply supported girder bridges are predominantly based on local reinforcement, which limits their effectiveness in improving global structural performance. To address this limitation, a novel strengthening approach, namely the Method of Plate–Truss Combination Reinforcement (MPTCR), is proposed to transform the structural force system. In this method, steel trusses and a bridge deck system are integrated with the existing girder through reliable connectors to form a plate–truss composite system (PTCS), thereby enhancing stiffness and redistributing internal forces. An engineering case study is investigated using finite element analysis and field dynamic load testing. The results show that the fundamental frequency increases by 31.5% after strengthening, while the deflection is reduced by 38.2%. The measured fundamental frequency (9.452 Hz) agrees well with the numerical result (8.883 Hz), with a relative error of 6.4%. Moreover, the measured impact coefficients are significantly lower than the code-based value, indicating improved dynamic performance. The findings demonstrate that the proposed method effectively enhances global stiffness, mitigates tensile stress in the original girder, and improves the dynamic behavior of the structure. This study provides a practical and efficient solution for the rehabilitation of aging girder bridges.